Besieged fortress syndrome as an element in building the emotions of populism - Ziółkowski, Jacek (Society Register, 2022)
The aim of this paper is to show the relationship between the besieged fortress syndrome, understood as a specific social engineering tool, and populism understood as a type of propaganda narrative. Particular attention has been paid here to the emotional aspect related to arousing the atmosphere of the siege. These are negative emotions, which in the siege syndrome are directed beyond the boundaries of the social system, and in the case of populism, negative emotions are directed towards the indicated intra-system entities. An important assumption is a thesis that negative emotions in both phenomena constitute only a starting point for arousing positive emotions towards the community subjected to socio-technical pressure, and above all, positive emotions that are supposed to create a strong bond between the political leader, the propaganda promoter of the threat, and their supporters or followers.